Une clavicule et un nouveau fragment mandibulaire d'Australopithecus Prometheus - Boné, Edouard L. (Bernard Price Institute for Palaeontological Research, 1955)
An acromial fragment of a collar.-bone of Australopithecus prometheus was found at the Limeworks Cave, Makapansgat (N. Transvaal). This specimen, which is the first ever discovered of the Australopithecine clavicle, is described and compared with both human (fossil and recent) and anthropoid bones. A left fragment of a lower jaw with a perfectly preserved and moderately worn third molar of the Makapan ape-man, found during the same sorting operation of the dumps (April 1955), is discussed here: size and pattern emphasize the homogeneity of the prometheus finds, their close relationship to Teianthropus, and their human affinity.
Main article
Keywords: Clavicule, Australopithecus prometheus, collar bone, Limeworks Cave, Makapansgat